(untitled) (University of Khartoum Engineering Journal, 2022)
In this paper methods for determination of maximum local scour depth and eroded material volume downstream of highway drainage structures were developed. Severe local scour leads to undermining followed by collapsing of the drainage structure. The analysis method is based on integrating a new technique of improved drainage structure outlet geometry, jet hydraulic characteristics and soil properties. The jet velocity, induced shear stress, critical shear resistance to erosion and particle size are the main factors that control the erosion process downstream of a drainage structure. The study is of experimental and theoretical nature. The developed mathematical model was calibrated using collected field data in addition to laboratory tests. The produced scour holes were plotted for each laboratory run and the scour hole depth, width and length were measured. A semi- empirical relation has been developed for predicting the depth of local scour hole. It is based on Densimetric Froude number. It is found that the semicircular apron gives less scour depth and width when compared to the linear front apron. The comparison of the model outputs and field study is found of a good agreement. The model is recommended for engineering design of highway drainage structures located on streams of sandy bed.